Boron Neutron Capture Therapy: Current Status and Challenges - Wang, Song; Zhang, Zhengchao; Miao, Lele; Li, Yumin (Frontiers in Oncology, 2022)
Boron neutron capture therapy (BNCT) is a re-emerging therapy with the ability to selectively kill tumor cells. After the boron delivery agents enter the tumor tissue and enrich the tumor cells, the thermal neutrons trigger the fission of the boron atoms, leading to the release of boron atoms, leading to the release of the α particles (4He) and recoil lithium particles (7Li), along with the production of large amounts of energy in the narrow region. With the advantages of targeted therapy, low toxicity, BNCT has become a unique method in the field of radiotherapy. Since the beginning of the last century, BNCT has been emerging worldwide and gradually developed into a technology for the treatment of glioblastoma multiforme, head and neck cancer, malignant melanoma and other cancers. At present, how to develop and innovate more efficient boron delivery agents and establish a more accurate boron-dose measurement system has become the problems faced by the development of BNCT. We discuss the use of boron delivery agents over the past several decades and the corresponding clinical trials and preclinical outcomes. Furthermore, the discussion brings recommendations on the future of boron delivery agents and this therapy.